Correlation between adenoidal nasopharyngeal ratio and symptoms of enlarged adenoids in children with adenoidal hypertrophy - Taiwo Olugbemiga Adedeji; Yemisi B Amusa; Ademola A Aremu (Wolters Kluwer Medknow Publications, 2016)
Background: Adenoid hypertrophy is one of the most common health problems affecting the paediatric population. This study aims to correlate adenoidal nasopharyngeal ratio (ANR) with symptoms of enlarged adenoids in children with enlarged adenoids. Materials and Methods: It was a year, cross-sectional, hospital-based study conducted at Lautech Teaching Hospital, Osogbo. ANR was determined by dividing adenoidal depth with nasopharyngeal depth on the plain lateral radiographs. Results: A total of 90 consecutive children consisting of 61 males and 29 females were included in the study with M:F ratio of 2.1:1. Their ages ranged from 8 months to 11 years. All the patients presented with nasal obstruction, mouth breathing and noisy breathing. Majority (64.5%) had severe obstructions with preponderance among children of 3-5 years (39.9%). Linear regression analysis showed significant association between age and ANR (t = 10.447, P < 0.001). There was high significant association (P < 0.05) between presenting symptoms and degree of nasopharyngeal airway obstruction; for snoring (r = 0.251, P = 0.000), sleep apnoea (r = 0.594, P = 0.000), nasal discharge (r = 0.314, P = 0.001), excessive daytime sleepiness (r = 0.219, P = 0.019) and failure to thrive (r = 0.240, P = 0.011). Conclusion: Lateral X-ray of the nasopharynx is an effective tool to evaluate children with suspected adenoid hypertrophy. It correlates well with patients' symptoms and provides objective measures of adenoid hypertrophy.